Intellectual Capital, Nilai Perusahaan dan Profitabilitas sebagai Variabel Mediasi - Widyati, Ni Ketut Ari; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 33 No 12 (2023), 2023)
Optimizing company value is the main goal of establishing a company. This research aims to obtain empirical evidence about the influence of intellectual capital on the value of banking companies listed on the Indonesia Stock Exchange in 2018-2021 which is mediated by profitability. There are 3 theories used in this research, namely agency, stakeholder and resource theory. The population in this study was 49 banking companies with 28 companies selected as samples using the purposive sampling method. The data was then analyzed using path analysis techniques, with SPSS 26.0 for Windows software. The results of the analysis prove that intellectual capital has no effect on company value, intellectual capital has a positive effect on profitability, profitability has a positive effect on company value, and profitability is proven to mediate the effect of intellectual capital on company value. Keywords: Intellectual Capital; Profitability; Firm Value